Comparing the Senior and Vocational High School Students’ Speeches through Thematic Progression - Utama, Afrian Restu (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2024)
Public speaking is vital in the 20th century. Mastering public speaking can benefits in either work and education setting. Speech is an example of public speaking that commonly used as in an English competition. A good speech can be seen from its cohesion and coherence. This study aims to analyze the students’ ability in maintaining the cohesion and coherence in their speeches in an English speech competition. The data of this study was taken from two YouTube videos from Erlangga Inspirasi channel. Four speeches from each video were taken randomly. The speeches were transcribed into written form and analyzed using the theory of thematic progression. The results of the analysis were validated by an expert in SFL field. The result showed that all thematic progression are realized in all speeches. The constant patterns are rarely found in both senior and vocational high school students’ speeches. This finding is different with the previous studies regarding the thematic progression. The multiple patterns are mostly found in senior high school students’ speeches. This indicates that they have a good ability to develop a cohesive and coherent text. Meanwhile, the linear patterns are mostly found in vocational high school students’ speeches. This indicates that they can maintain a good cohesion although it is not as good as the senior high school. Several challenges are also found. Few clauses were failed to develop which led the text become less cohesive and coherent. This highlight the importance of applying thematic progression in English language teaching activity.